MENINGKATKAN KETERAMPILAN ILMIAH SAINS MELALUI KEGIATAN ONE DAY ADVENTURE PADA MATERI TUMBUHAN HIJAU DI KELAS V SDN JURUBANU - Filajuni Arta Rahmadana (Universitas Lambung Mangkurat, 2014)
Abstract. Methods One Day Adventure is a learning method developed from cooperative approach to the investigation group (Group Investigation). This study on the application of methods One Day Adventure at SDN Jurubanu on the subjects of Science. The research objective is to improve the scientific skills of students, increase the activity of teachers and students in the green plant material. Scientific skills are the main objectives of this research are mangamati skills, ask questions, make hypotheses, conduct observations, interpret and communicate. Subjects in this study were students of class V SDN Jurubanu totaling 14 people. The study design consisted of two cycles and each cycle consisting of 2 meetings. The results showed that: (1) an increase in scientific skills of students in each meeting, and the most developed skill is the skill of observation. (2) the quality of the teacher's activities increased from 41.5 category is very less in cycle 1 meeting 1 to 65 category is quite active in cycle 2 meeting 2, and (3) an increase in the activity of students in each cycle, cycle 1 meeting 1 scored the mean 54.1 average less active category while in the second cycle 2 meeting increased to 73.0 categories. Thus, it can be said that the method of One Day Adventure can improve scientific skills, activities of teachers and students of SDN Jurubanu activity.Keywords: teacher activities, student activities, scientific skills, methods One Day Adventure